Collaborative Governance dalam Penanganan Anak Korban Kekerasan Seksual di Kabupaten Nganjuk - Lylu Tirta Damayanti; Bagus Nuari Harmawan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research aims to analyze the implementation of collaborative governance in handling child victims of sexual violence in Nganjuk Regency. Sexual violence against children is a serious issue that requires the involvement of various parties, including the government, law enforcement agencies and the community. Through a qualitative approach with a case study method, this research explores the dynamics of collaboration between the Social Service and Nganjuk Police in providing protection and rehabilitation for victims. The research results show that although collaborative efforts have improved services and community awareness, there are still significant barriers such as lack of community participation and limited resources. This research emphasizes the importance of building a strong framework for collaboration that can increase trust, shared understanding, and commitment between stakeholders. Recommendations for improving collaboration include increasing public awareness campaigns, training for service providers, and allocating adequate funding for child protection initiatives. This research contributes to the understanding of the collaborative governance framework in child protection and provides insight for policy makers to strengthen responses to sexual violence against children.